Pharmacological properties of glabridin (a flavonoid extracted from licorice): A comprehensive review. (October 2021) - Li, Chun-xiao; Li, Tian-hao; Zhu, Mei; Lai, Jiang; Wu, Zhi-peng
Graphical abstract: Highlights: Glabridin has a wide range of pharmacological effects. There is a disagreement on whether glabridin has estrogenic effects. Glabridin can be used to improve the pharmacokinetic characteristics of other medicines. It is necessary to carry out more clinical studies to confirm the pharmacological effects. Abstract: Licorice, a widely used traditional Chinese medicine, contains many bioactive components. Glabridin is a major flavonoid extracted from the root of licorice and has a wide range of pharmacological properties including anti-inflammatory, anti-cancer, anti-bacterial, regulating blood lipids and blood glucose levels, neuroprotection, anti-osteoporosis, and phytoestrogen effects. At present, these studies are mostly based on cell and animal experiments. It is necessary to carry out more clinical studies in the future. In addition, there is a disagreement on whether glabridin has estrogenic effects. Also, it is generally believed that glabridin regulates blood lipids and blood glucose metabolism by activating the expression of PPARγ and C/EBPα. However, research has shown that glabridin-based licorice extract can inhibit the expression of PPARγ and C/EBPα. Pharmacokinetic research shows that glabridin is easily absorbed by the human body, and the inhibitory effects of glabridin on some metabolic enzymes can improve the pharmacokinetic characteristics of other medicines.